Agency in the Reconstruction of Language Identity: A Narrative Case Study from the Island of San Andrés (GIST – Education and Learning Research Journal, 2014)
The adoption of the English language paradigm and the subsequent implementation of bilingual policies worldwide are generating new linguistic hierarchies. These have an effect on the linguistic diversity at the sub-national level and on individuals’ linguistic human rights. This article reports the results of a case study on an individual’s re-engineering of his in-group language identity. Through the analysis of a narrative written by the participant (Fidel), this article intends to show the effects of language ideologies on the discursive and sociocultural practices of a member of a raizal community from San Andrés (Colombia). As a multilingual individual surrounded by multiple ideologies of language, covert and overt language policies, and language hierarchies of prestige dictated by a scope larger than his immediate social group, Fidel preserves, challenges, and transforms his in-group linguistic identity.
Keywords: Linguistic identity; language policies; linguistic human rights